Clustered DNA damage, influence on damage excision by XRS5 nuclear extracts and Escherichia coli Nth and Fpg proteins. - David-Cordonnier, M; Laval, J; O'Neill, P (2000)
Ionizing radiation and radiomimetic anticancer agents induce clustered DNA damage, which are thought to reflect the biological severity. Escherichia coli Nth and Fpg and nuclear extracts from XRS5, a Chinese hamster ovary Ku-deficient cell line, have been used to study the influence on their substrate recognition by the presence of a neighboring damage or an abasic site on the opposite strand, as models of clustered DNA damage. These proteins were tested for their efficiency to induce a single-strand break on a (32)P-labeled oligonucleotide containing either an abasic (AP) site, dihydrothymine (DHT), 7,8-dihydro-8-oxo-2'deoxyguanine, or 7, 8-dihydro-8-oxo-2'deoxyadenine at positions 1, 3, or 5 base pairs 5' or 3' to either an AP site or DHT on the labeled strand. DHT excision is much more affected than cleavage of an AP site by the presence of other damage. The effect on DHT excision is greatest with a neighboring AP site, with the effect being asymmetric with Nth and Fpg. Therefore, this large inhibition of the excision of DHT by the presence of an opposite AP site may minimize the formation of double-strand breaks in the processing of DNA clustered damages.